SICAD 88 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The Second International Exhibition on Cooperation and Development will be held 'from December 7-11, 1988 in Montpellier, France. Businesses, NGOs, governmental and quasi-governmental organizations, international organizations and the media who...